Impact of oral anticoagulation therapy on postoperative atrial fibrillation outcomes: a systematic review and meta-analysis - Mariana Fragão-Marques (BMC, 2021)
Abstract Background Post-operative atrial fibrillation (POAF) is the most common complication after cardiac surgery. Recent studies had shown this phenomenon is no longer considered transitory and is associated with higher risk of thromboembolic events or death. The aim of this study was to systematically review and analyze previous studies comparing oral anticoagulation therapy with no anticoagulation, regarding these long-term outcomes. Methods PubMed/MEDLINE, EMBASE, Web of Science and Cochrane Database were systematically searched to identify the studies comparing the risk of stroke, or thromboembolic events or mortality of POAF patients who received anticoagulation compared with those who were not anticoagulated. Incidence of stroke, thromboembolic events and all-cause mortality were evaluated up to 10 years after surgery. Time-to-event outcomes were collected through hazard ratio (HR) along with their variance and the early endpoints using frequencies or odds ratio (OR). Random effect models were used to compute statistical combined measures and 95% confidence intervals (CI). Heterogeneity was evaluated through Q statistic-related measures of variance (Tau2, I2, Chi-squared test). Results Eight observational cohort studies were selected, including 15,335 patients (3492 on Oral Anticoagulants (OAC) vs 11,429 without OAC) that met the inclusion criteria for qualitative synthesis. Patients had a wide gender distribution (38.6–82.3%), each study with a mean age above 65 years (67.5–85). Vitamin K antagonists were commonly prescribed anticoagulants (74.3–100%). OAC was associated with a protective impact on all-cause mortality at a mean of 5.0 years of follow-up (HR is 0.85 [0.72–1.01]; p = 0.07; I2 = 48%). Thromboembolic events did not differ between the two treatment arms (HR 0.68 [0.40–1.15], p = 0.15). Conclusion Current literature suggests a possibly protective impact of OAC therapy for all-cause mortality in patients with new-onset atrial fibrillation after cardiac surgery. However, it does not appear to impact thromboembolism rate.